First astrometric reduction of Cassini Imaging Science Subsystem images using an automatic procedure: application to Enceladus images 2013–2017. Issue 1 (4th September 2018) - Zhang, Q F; Lainey, V; Cooper, N J; Vienne, A; Peng, Q Y; Xiong, Y T
ABSTRACT: We provide new astrometric observations of Enceladus from images taken using the Cassini Imaging Science Subsystem (ISS) Narrow-Angle Camera. Astrometric reduction was performed using a new fully automatic camera repointing technique built within the Caviar software package. The new automatic procedure is based on the k-d tree technique and has been developed as an alternative to the manual technique currently available in Caviar . We describe the new procedure and demonstrate its effectiveness compared with manual processing. Repointing corrections were computed using reference stars from the UCAC4 and Gaia DR1 star catalogues. We compare the observed-minus-computed (O−C) residuals of Enceladus based on UCAC4 with those based on Gaia DR1, relative to the JPL SAT375 ephemeris and the IMCCE NOE ephemeris, respectively. We reduced all available Cassini ISS images of Enceladus during the period 2013–2017, producing a total of 1109 Cassini -centred astrometric observations. These are provided in right ascension ( α ) and declination ( δ ) in the International Celestial Reference Frame (ICRF). Estimated mean O−C residuals relative to JPL's SAT375 ephemeris were 0.7 km in α  × cos( δ ) and 1.8 km in δ, with standard deviations of 2.4 and 3.2 km, respectively. No improvement in the precision of the observations was obtained when using the GAIA DR1 star catalogue compared with UCAC4.